2004
DOI: 10.1108/03068290410561168
|View full text |Cite
|
Sign up to set email alerts
|

Child income poverty and child deprivation: an essay on measurement

Abstract: This paper is a study on child poverty from two perspectives: child income poverty (derived from family income) and child deprivation (evaluated by non-monetary indicators). On the one hand, empirical evidence supports the thesis that income-based poverty measures and deprivation measures do not overlap. On the other hand, the relationship between poverty and the child's living conditions is not linear. Uses micro-econometric techniques to analyse child income poverty and present deprivation indicators, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 16 publications
3
40
0
Order By: Relevance
“…A cross-country study in four countries in the European Union (EU) finds that children living in monetary poor households are not necessarily those suffering from deprivation in non-monetary dimensions, and vice versa (Roelen and Notten, 2013). Analogous observations were made for children in Portugal (Bastos et al, 2004). With respect to child poverty in the UK, Brewer et al (2009) find that as household income rises, children's levels of deprivation first rise and then fall.…”
Section: Association and Mismatch Of Monetary And Multidimensional Chmentioning
confidence: 92%
“…A cross-country study in four countries in the European Union (EU) finds that children living in monetary poor households are not necessarily those suffering from deprivation in non-monetary dimensions, and vice versa (Roelen and Notten, 2013). Analogous observations were made for children in Portugal (Bastos et al, 2004). With respect to child poverty in the UK, Brewer et al (2009) find that as household income rises, children's levels of deprivation first rise and then fall.…”
Section: Association and Mismatch Of Monetary And Multidimensional Chmentioning
confidence: 92%
“…Health is obviously of the utmost importance as a dimension of child well-being and its inclusion in a child well-being index is unquestionably found in a vast majority of studies on the matter (e.g., Land et al 2001Land et al , 2007Bastos et al 2004Bastos et al , 2008Bradshaw et al 2007;4 Questionnaires are available upon request to the corresponding author. 5 Income categories in the questionnaire were defined according to the Portuguese National Statistics Institute's (INE 2008) categorization of the annual total net income of households, divided by the twelve months of the year in order to obtain monthly income.…”
Section: Choosing the Dimensions Of Child Well-beingmentioning
confidence: 99%
“…Research has shown that housing conditions affect children's well-being (see e.g., Aber et al 2002;Hoelscher 2004;Bradshaw et al 2007), so indicators related to physical housing problems, such as rotten windows, having a flushing toilet and a shower/bathtub (Bradshaw et al 2007;Bradshaw and Richardson 2009), as well as indicators related to overcrowding and specifically to the child having or not his/her own private space in the house (Hoelscher 2004;Bastos et al 2004Bastos et al , 2008Bradshaw et al 2007;Bastos and Machado 2009;Bradshaw and Richardson 2009), emerge as relevant.…”
Section: Choosing the Dimensions Of Child Well-beingmentioning
confidence: 99%
See 2 more Smart Citations